"Armed and disarmed" theory in the addition of an azide radical to glucals1. Issue 48 (28th May 2015) - Wang, Wenjun; Yang, Zhongyue; Xu, Yun; Liu, Taibao; Song, Tianbang; Zhao, Yunyan; Xu, Xiufang; Zhao, Wei; Wang, Peng George
<x xml:space="preserve">Abstract</x> "Armed" glucals were prone to undergo kinetic process. The torsional strains govern the selectivity. Meanwhile, "disarmed" glucals preferred thermodynamic radical addition. A sialic acid containing trisaccharide was also synthesized by the method.